On the effect of a global adoption of various fractions of biodiesel on key species in the troposphere. (5th April 2010) - Cooke, M.C.; Marven, A.R.; Utembe, S.R.; Archibald, A.T.; Ensor, G.W.R.; Jenkin, M.E.; Derwent, R.G.; O'Doherty, S.J.; Shallcross, D.E.
Biodiesel use is being promoted worldwide as a green alternative to conventional diesel. A global three-dimensional chemistry transport model is employed to investigate the impact on air quality and global tropospheric composition of adopting biodiesel as a fractional component of diesel use. Five global simulations are conducted where emission changes of hydrocarbons and nitrogen oxides were applied within the model to investigate changes in tropospheric pollutants. Hydrocarbon emission reductions lead to an overall improvement in air quality with reductions in ozone, organic aerosol, aromatic species and PAN. However when the increase in NOx, caused by increased exhaust temperature, is included there is negligible difference in ozone production between mineral diesel and biodiesel blends. The cause of these effects is discussed. [Received: September 30, 2009; Accepted: December 12, 2009]